(untitled) (Research, Society and Development, 2020)
This article aims to identify, through a narrative review of literature, the general objective of treatment for patients with Borderline Personality Disorder (BPD), based on interventions of the Schema Therapy (ST) and to identify the predominant modes in patients with this disorder. The search for data for analysis occurred through consultations on digital platforms and from books, by authors considered as references in the themes. As a result of the analyzed articles, it appears that Scheme Therapy has shown effectiveness in the psychological treatment for Borderline Personality Disorder, emphasizing the cognitive and emotional levels of the patient with this disorder. It is evident that the predominant schematic modes are the abandoned child, angry child, punitive parents, disconnected protective mode and hypercompensation modes. It is concluded that the techniques used by therapists allow the identification of which emotional needs were not met during childhood and adolescence, the main goal of ST for BPD, is to fortify the healthy adult mode.